Web and Mobile-Based Online Watch Auction Application Using Waterfall Method - Alfian Nur Kusuma; Anita Fira Waluyo (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The advancement of mobile technology has driven the creation of digital solutions that simplify various activities, including the auction process. This study aims to design and develop a mobile-based online watch auction application using Flutter as the user interface development framework. In addition to the mobile application for users, a web-based admin dashboard was also developed to manage auction data, including creating auctions. The backend system was developed using Node.js with PostgreSQL as the database management system. The mobile application provides key features such as user registration, login, viewing auction lists, placing bids, and viewing bidding history. Meanwhile, the web admin system enables administrators to manage auction items and monitor the auction process efficiently. The test results show that the main features function according to user needs, and the system runs stably on both mobile devices and web platforms. This application is expected to serve as a practical and easy-to-use digital auction platform.